Estudo bioquímico de fitase, protease e xilanase produzidas por fungos filamentosos usando fontes de carbono alternativas: comparação com as enzimas comerciais e aplicação na alimentação animal - ANA LORENA DE OLIVEIRA SIMAS (2023)
In recent decades, the manufacture of animal feed began to replace the use of animal proteins with vegetable protein sources. However, many plant-based ingredients contain anti-nutritional factors such as non-starch polysaccharides, phytates and others. In this way, enzymes are added to the feed to increase the availability of food nutrients, promote animal growth and improve zootechnical productive performance. Therefore, this study was carried out with the objective of selecting and characterizing the fungus with the best production of phytase, protease and xylanase, applying these enzymes in different foods and comparing them with commercial enzymes. Seven filamentous fungi of the genera Aspergillus sp and Thermoascus sp were used in semi-solid cultivation using alternative carbon sources. The best phytase producers were A. niveus in brown rice followed by Aspergillus sp. M2 in rice straw. The best protease producers were Aspergillus sp. M2 on rice straw, followed by A. flavus on wheat bran. In xylanase, the best producers were A. niveus on brown rice, followed by Aspergillus sp. M2 in rice straw. The growth time test showed the peak of phytase production in A. niveus at 144 hours (3.14 U/mg) of incubation in rice straw, as well as for xylanase production with a maximum production of 11.53 U/mg. Protease peaked at 96 hours with A. niveus (2.67 ± 0.35 U/mg) in rice straw. Subsequently, the enzymatic characterization was performed regarding pH and optimum temperature using A. niveus grown on rice straw. The phytase produced showed a peak of activity at pH and temperature of 4.5-5 and 45°C, respectively. The optimal peak temperature and pH for proteases were 50°C and pH 6, and for xylanases and 45°C and pH 5, respectively. The in vitro activity in animal feed was determined in µmol/mL of released product, and the phytase from A. niveus was better in FT (wheat bran) with 2.21 ± 0.15 µmol/mL, whereas the commercial phytase showed better activity on FA (rice bran) with 1.86 ± 0.04 µmol/mL. The in vitro protease activity of A. niveus showed greater activity in FA with 8.34 ± 0.76 µmol/mL, the commercial protease showed better results in DAF food (alternative diet - pure fiber) with 5.57 ± 0.14 µmoles/mL. The in vitro activity of A. niveus xylanase showed high levels of enzymatic activity, standing out in the MI food (corn) with 96.55 ± 6.79 µmol/mL, whereas commercial xylanase stood out in the degradation of FT with 31.05 ± 3.85 µmol/mL of released sugar. In this way, enzymes were produced that, if added to animal feed, may be able to improve the availability of nutrients in non-ruminant animals.